THE INFLUENCE OF FEED DIFFERENCES ON CAPTURE RESULTS IN THE PUBE CAPTURE IN THE RANTAU BARU VILLAGE PANGKALAN KERINCI DISTRICT OF PELALAWAN RIAU PROVINCE - Dila Asfariani; Arthur Brown; Jonny Zain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractThe study of the influence of different bait on the catch of bubu (kabam pantau) was conducted 10 days on May 1 to May 10 2019 in Rantau Baru Village, Pangkalan Kerinci District, Pelalawan Regency, Riau Province. This study aims to compare the bait on the trap fishing tool (Kabam pantau) namely coconut pulp (U1), rice bran bait (U2) and Kroto ant egg bait (U3) to the catch. The method used is an experimental fishing method to support this method by collecting data through direct observation, interviews and documentation. Data that is processed and processed using t test analysis. The three types of bait used there are effects of providing different types of bait on the catch. Coconut pulp feed (U1) obtained the results of the number of 548 individuals with a weight of 2080 grams, rice bran bait (U2) in the number of 1228 individuals with a weight of 3450 grams, and Kroto ant egg bait (U3) with 1222 individuals with a weight of 3435 grams.Keywords: Effect of Bait,Floating Bubu, Catch Results